Deneysel vitreus materyalleri [Experimental Vitreous Substitutes] - (:unkn) unknown (Gazi Eye Foundation, 2020)
Vitreous substitutes have been used for many purposes such as tamponade during vitreoretinal surgeries for retinal detachment, complications of diabetic retinopathy, macular hole and retinal bleeding involving the posterior segment of the eye or such as a part of drug delivery system in new experimental studies and clinical trials. Current available vitreous substitutes such as silicone oils, heavy silicone oils and gases have a temporary effect to obtain ideal internal pressure for reattachment of the detached retina and short-term biocompatibility. For this reason, some chemists, engineers and ophthalmologists have considered about designing and producing an ideal vitreous substitute in recent years. Recent studies on biochemical, biomechanical and functional properties of the natural vitreous enabled the development of both more functional and biocompatible vitreous substitutes with long-term usability and fewer side effects. This article reviews the novel vitreous substitutes and their challenges and promising developments in future. © 2019 Gazi Eye Foundation. All rights reserved.
Keywords: Intravitreal drug; Retinal detachment; Vitreous; Vitreous substitutes